Fear of artificial intelligence initiated by religious feelings - Prodić, Slobodan (Napredak, 2024)
Artificial intelligence is a specific phenomenon which largely affects modern society. Being a relatively recent phenomenon, inside communities undergoing the desecularization process, artificial intelligence inevitably leads to the question as to how and in what way it has been accepted by believing people. Believers’ opinions about artificial intelligence are divided. In a number of them it causes fear and extremely negative feelings. The most frequent reason for it is the insufficient familiarity about what artificial intelligence is and what its place in modern society is. As for religious communities, huge responsibility about the attitude towards artificial intelligence is actually assumed by clergy and their willingness to speak about it to people they have been entrusted with for spiritual guidance.
Keywords: artificial intelligence; religion; fear